Advances in Surface-Enhanced Raman Spectroscopy for Therapeutic Drug Monitoring - Huasheng Lai; Xinlan Wang; Menghan Qi; Hao Huang; Bingqiong Yu (Molecules)
Therapeutic drug monitoring (TDM) is pivotal for optimizing drug dosage regimens in individual patients, particularly for drugs with a narrow therapeutic index. Surface-enhanced Raman spectroscopy (SERS) has shown great potential in TDM due to high sensitivity, non-destructive analysis, specific fingerprint spectrum, low sample consumption, simple operation, and low ongoing costs. Due to the rapid development of SERS for TDM, a review focusing on the analytical method is presented to better understand the trends. This review examines the latest advancements in SERS substrates and their applications in TDM, highlighting the innovations in substrate design that enhance detection sensitivity and selectivity. We discuss the challenges faced by SERS for TDM, such as substrate signal reproducibility and matrix interference from complex biological samples, and explore solutions like digital colloid-enhanced Raman spectroscopy, enrichment detection strategies, microfluidic SERS, tandem instrument technologies, and machine learning-enabled SERS. These advancements address the limitations of traditional SERS applications and improve analytical efficiency in TDM. Finally, conclusions and perspectives on future research directions are presented. The integration of SERS with emerging technologies presents a transformative approach to TDM, with the potential to significantly enhance personalized medicine and improve patient outcomes.